Statistical Characterization of the Phytochemical Characteristics of Edible Mushroom Extracts. (3rd May 2018) - Buruleanu, Lavinia Claudia; Radulescu, Cristiana; Georgescu, Andreea Antonia; Danet, Florin Andrei; Olteanu, Radu Lucian; Nicolescu, Cristina Mihaela; Dulama, Ioana Daniela
ABSTRACT: The antioxidant activity, total phenolic content, and total flavonoid content of 10 edible mushrooms species, including cultivated ( Pleurotus ostreatus, Agaricus bisporus white and brown) and wild ( P. ostreatus, Macrolepiota procera, Cantharellus cibarius, Russula vesca, Russula alutacea, Boletus edulis and Agaricus campestris ), were determined. The extraction was performed using water and 50% water–ethanol and the caps and stipe were investigated separately. Water was the most appropriate solvent for phenolic compounds regardless of the sample. In contrast, the presence of ethanol in the solvent increased the extraction of flavonoids for cultivated P. ostreatus (caps and stipe), and wild R. alutacea, R. vesca, A. campestris, P. ostreatus (only caps) and C. cibarius, M. procera (only stipe). Significant differences between the antioxidant activities of the samples were registered in relationship with the different solvents. The antioxidant activity of water extract of dried A. bisporus brown (cultivated) showed the strongest 1, 1-diphenyl-2-picrylhydrazyl radicals-scavenging assay (88.64%), while the B. edulis hydroalcoholic extract contained 74.93%. A detailed investigation into the functional group of phenolics and other organic compounds responsible with the antioxidant activity has been performed using Fourier transform infrared spectroscopy. The infrared spectra showed that the solvent-type directly influences the extraction process and, hence, the antioxidant activity. The present study contributes to information concerning mushrooms as sources of biologically active compounds. To investigate the correlations between phytochemical characteristics (i.e., phenolics, flavonoids and antioxidant activity) closely related to nature of solvents, the statistical analysis was performed.